Do we need an open face recognition search engine? - Cammozzo, Alberto (2012)
The wide application of face recognition technology may expose us to unforeseen situations. Our ability to cope with this technological innovation may have important consequences for human rights and citizens privacy. One of the most bothering issues is information asymmetry being introduced not only in the web, but also in real life situations. Some imaginary situations are listed, along with the technical and normative means to restore information symmetry. One of the possible solutions being the creation of an openly accessible face recognition search engine.